Development and characterization of pomegranate and orange fruit peel extract based silver nanoparticles - Vinay, C.H.; Goudanavar, P.; Acharya, A. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Nanoparticles are those whose size ranges 1 nm to 100 nm. They are in different sizes and shape, such as triangular, spherical, irregular, etc. In recent years, nanoparticles synthesis has received considerable attention due to their unique properties and potential applications. Powdered sample (100gm)was extracted with 800ml ethanol by Soxhlet extraction method for 6 hours. The resultant extract was used to prepare nanoparticles. Methods: The main objective of the present work was to prepare pomegranate and orange peel extract based nano particles by chemical complexation method. Ethanolic extracts of pomegranate and orange peel were prepared by using Soxhlet apparatus and evaluated for phyto-chemical constituents. Results: Qualitative analysis of pomegranate peel showed positive results for Alkaloids, Anthraquinones, Saponins and Terpenoids, where as orange peel showed positive results for Alkaloids, Tannin and Saponins. The percentage moisture content obtained from the 2 fruits (pomegranate and orange) was 72% and 96.12% respectively. The pH was found to be 3.6 and 3.8 for pomegranate and orange respectively. A zeta potential of prepared nanoparticles for pomegranate extract was found in the range of -24.6 mV to -34.5 mV (P20 & P50) and -21.4 mV to 32.0 mV (O20 & O50) for orange extract, respectively. These values of nanoparticles having higher surface charge which indicates there is least chance of aggregation. The particle size for pomegranate extract was found in the range of 118.6 nm to 231.7 nm (P20 & P30) and 178.8 nm to 191.6 nm (O20 & O50) for orange extract, respectively. These range confirms that obtained particles were in nano range, i.e. <500 nm size. SEM results indicated the formation of nanoparticles and were relatively spherical in shape. Energy dispersive spectrometry (EDS) analysis confirms the presence of AgNPs. Conclusion: The silver nanoparticles were prepared by using fruit peels extract of pomegranate and orange. Computability study FT-IR showed no any change of functional groups of peel extracts in prepared nanoparticles. Zeta potential showed higher value hence less particle aggregation. Prepared nanoparticles were spherical in shape and having particle size of approximately 200±20nm. Further the study will be extended for anti-microbial and wound healing activities. JMMIHS,2018;4(1):72-85